2014
DOI: 10.1002/rra.2823
|View full text |Cite
|
Sign up to set email alerts
|

Why do fish strand? An analysis of ten years of flow reduction monitoring data from the Columbia and Kootenay rivers, Canada

Abstract: Stranding of fish due to flow reductions has been documented in the near shore of the Columbia and Kootenay Rivers, Canada, and can result in sub-lethal or lethal effects on fish. Ten years (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)) of monitoring data have been collected at sites below two hydro-electric dams (Hugh-L-Keenleyside and Brilliant Dam) following flow reductions. A generalized linear mixed effects model analysed the probability of a stranding event in relation to environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…Studies have shown that stranding is species-and size-selective, whereby recently emerged fry are the most vulnerable life-history stage [15,52,56,57]. This finding is supported by the analysis of ten-year flow downramping monitoring data of Canadian rivers, showing that the highest stranding probabilities occur from May to August when juveniles inhabit nearshore areas which are likely to be dewatered [50]. Field surveys at the Drava River, Austria, revealed 50-500 stranded larvae of European grayling (Thymallus thymallus) per 100 m shoreline after single hydropeaking events [58].…”
Section: Thresholds For Impact Mitigationmentioning
confidence: 91%
See 3 more Smart Citations
“…Studies have shown that stranding is species-and size-selective, whereby recently emerged fry are the most vulnerable life-history stage [15,52,56,57]. This finding is supported by the analysis of ten-year flow downramping monitoring data of Canadian rivers, showing that the highest stranding probabilities occur from May to August when juveniles inhabit nearshore areas which are likely to be dewatered [50]. Field surveys at the Drava River, Austria, revealed 50-500 stranded larvae of European grayling (Thymallus thymallus) per 100 m shoreline after single hydropeaking events [58].…”
Section: Thresholds For Impact Mitigationmentioning
confidence: 91%
“…After alevins have absorbed the major portion of their yolk sack, they emerge as fry from the substrate [19,20]. During this early ontogenetic development, they are very susceptible to pulsed-flow operations as they utilize high-risk habitats in the ramping zone and have little swimming capacities, entailing drift and stranding of individuals [5,6,[50][51][52][53]. In the Saltdalselv River, Norway, high flows during the alevin and fry stage significantly increased the mortality of Atlantic salmon and brown trout [54].…”
Section: Fry Emergence and Early Juvenile Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of field experiments (usually without control, though) have been performed to assess the stranding rate and to assess the conditions when stranding prevail [7] [14] [15] [16] [17]. Important factors affecting stranding rates in young wild Atlantic salmon (Salmo salar) and brown trout (Salmo trutta) were water temperature, time of year, time of day, minimum discharge, wetted history, shape of the river bed, and dewatering rate [17] [18] [19] [20]. However, death is not necessarily a consequence of stranding.…”
mentioning
confidence: 99%